Привычка выживать: [повести] - Некрасова Мария Евгеньевна (Большая книга ужасов '79, 2020)
Экземпляры: ф.3 (20201203☮) / Инвентарный номер: 59614 / Цена: 255.00 / Авт.знак: Н 48 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6